Analisis dan Perancangan SIM BUMDes Benan Bahari, di Desa Benan, Kabupaten Lingga, Provinsi Kepri - Kusasi, Firmansyah; Paramita, Bunga; Akhirman, Akhirman (Bahtera Inovasi, 2023)
This report focuses on the Indonesian and ASEAN maritime markets. Indonesia's wide network of islands and key location in Southeast Asia have a considerable impact on its transportation system, economy, and trade. The shipping industry contributes significantly to the expansion of the global economy. ASEAN emphasizes the importance of the maritime industry in fostering economic progress and regional integration. Recent discussions at the ASEAN Maritime Forum included environmental concerns, vessel security, cyberattacks on maritime infrastructure, and regional collaboration in relation to maritime transport. Previous research has emphasized the efforts made by nations such as Malaysia, Singapore, Vietnam, Myanmar, Cambodia, Indonesia, Thailand, and the Philippines to enhance their maritime sectors. The purpose of this paper is to examine the current situation of the shipping market in Indonesia and other ASEAN nations, as well as the problems and opportunities it brings.